2023
DOI: 10.1590/1807-1929/agriambi.v27n11p839-847
|View full text |Cite
|
Sign up to set email alerts
|

Liquid fertilizers on photochemical efficiency and gas exchange in yellow passion fruit under saline stress

Luciano R. Guedes,
Lourival F. Cavalcante,
Antônio G. de L. Souto
et al.

Abstract: The Northeast region of Brazil is the primary producer of yellow passion fruit. In recent years, water scarcity has led passion fruit growers to use highly saline water for cultivation. Therefore, implementing technologies that alleviate the negative effects of salt stress on plants is a promising approach, particularly in semi-arid conditions. This study aimed to assess the efficacy of organomineral fertilizers in mitigating salt stress effects on chlorophyll-a fluorescence and gas exchange in ‘Guinezinho’ ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…This reduction in qP may be related to both the lower chlorophyll content and the negative effects of the excessive amount of sodium ions present in cells, ultimately causing damage to the photosystems (Zhang et al, 2019). On the other hand, the increase in qN constitutes a defense mechanism for plants to protect themselves from photoinhibition, in which they begin to dissipate the excess energy of the PSII reaction center in a non-photochemical way (Guedes et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction in qP may be related to both the lower chlorophyll content and the negative effects of the excessive amount of sodium ions present in cells, ultimately causing damage to the photosystems (Zhang et al, 2019). On the other hand, the increase in qN constitutes a defense mechanism for plants to protect themselves from photoinhibition, in which they begin to dissipate the excess energy of the PSII reaction center in a non-photochemical way (Guedes et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the impact of the nanobiostimulant, it was observed that the concentration of 272 mg L -1 resulted in the highest electron transport rate (Figure 6B) and 220 mg L -1 was the one that led to the lowest non-photochemical quenching (Figure 6D), promoting an increase of 12.7% and a decrease of 9.9% compared to the concentration of 0 mg L -1 , respectively. Thus, the effectiveness of the nanobiostimulant in increasing photosynthesis is observed, with much of the energy investment concentrated in processes that lead to increased photosystem yield (Guedes et al, 2023).…”
Section: Resultsmentioning
confidence: 99%